Catalytic Oxidation of 2-Mercaptoethanol by Cobalt(II)phthalocyanines Bearing Chalcone with Furan and Thiophene - Hüseyin Karaca (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Cobalt(II) phthalocyanines carrying on the four of the peripheral positionsfuran and thiophene as chalcones were sythesized. THF is used to investigate the catalyticoxidation of 2-mercaptoethanol. Thesynthesized phthalocyanines show catalytic activity on the oxidation of2-mercaptoethanol. Cobalt (II) phthalocyanine derived by chalcone with furanhas given catalytic specifications such as turnover number TON as 16.6, initialreaction rate as 0.293 μmol/secand the oxygen consumption as 10.06 μmol/min.The other cobalt (II) phthalocyanine derived by chalcone with thiophene hasgiven catalytic specifications such as turnover number TON as 15.9, initialreaction rate as 0.213 μmol/sec andthe oxygen consumption as 9.88 μmol/min. So chalcone derived phthalocyanines can be used as catalyst is oxidationof mercaptan by air.